A Novel Diagnostic Algorithm for Heparin-Induced Thrombocytopenia in a Retrospective Cohort of Lung Transplant Recipients. (March 2020) - Small, Bronwyn Larissa; Gomes, Marcelo P.; McCurry, Kenneth R.; Han, Xiaozhen; Ataya, Ali; Akindipe, Olufemi; Lane, C. Randall; Budev, Marie
Introduction: Heparin-induced thrombocytopenia (HIT) is characterized by thrombocytopenia and potential for thromboembolism. Lung transplant recipients are at risk of developing HIT due to heparin exposure peritransplant. We describe the incidence and impact of HIT in lung transplant recipient index hospital length of stay and survival. Design: A retrospective cohort was obtained from electronic medical records which were queried for all recipients treated with bivalirudin (institutional treatment of choice for HIT) between January 1, 2005, and February 16, 2017 (N = 1171). Patients who developed HIT >30 days after transplant or after their index transplant admission were excluded. A diagnostic algorithm was used retrospectively to determine clinical HIT with an intermediate or high pretest clinical suspicion ("4T" score ≥4) and either (1) positive anti-heparin–platelet-factor 4 (HPF4) assay and a positive functional platelet assay or (2) a positive HPF4 assay only, in patients who did not undergo cardiopulmonary bypass. Results: Among all lung transplant recipients, 2.1% were found to develop HIT in the peritransplant period (N = 25, mean = 88%) with a mean lung allocation score of 50.8 and an incidence of venous thromboembolism of 72%, most upper extremity in location. When matched with historical controls, patients with HIT had a longer overall index hospital length of stay of 43 days ( P = .008). There was no difference in short- or long-term survival posttransplant. Conclusion: Vigilance for the development of HIT in lung transplant recipients is necessary to prevent further morbidity from thromboembolic events. In our cohort, HIT increased hospital length of stay but did not appear to affect recipient survival.